(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The subject of this study is the description and study of mass riots that took place in the Republic of Kazakhstan. The chronology of mass riots is investigated, the mechanism of crimes committed and their stages are described, the types and classification of ways to counteract the investigation of crimes are determined, as well as methods and means of overcoming counteraction to the investigation of crimes